Implementation of Strict Liability in the Settlement of Environmental Disputes Based on the Job Creation Act (Analysis of Decision Number 102/PDT.G-LH/2021/PT PLK) - Haryo Sudrajat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Ministry of Environment and Forestry's lawsuit against PT. Kumai Sentosa (KS) over the fire in the defendant's oil palm plantation is the first environmental dispute in Indonesia with strict liability under Article 88 of the Job Creation Law. The existence of this Article was previously considered to confuse and even eliminate strict liability. This study aims to analyze the meaning strict liability Article 88 of the Job Creation Law and analyze its application in Decision Number 102/PDT.G-LH/2021/PT PLK. The results of the study show that based on the body and explanation, Article 88 of the Job Creation Law does not change the concept of strict liability into liability based on errors. This article also concludes that the court's interpretation of Article 88 of the Job Creation Law and its elucidation is a key factor in how courts construct strict liability. Partial meaning by only considering Article 88 of the Job Creation Law without relating it to the explanation of the article will greatly affect the construction of court evidence and bring it closer to the model of accountability based on errors or unlawful acts (PMH).